Design and Development of Smart Switching System for Controlling Home Appliances - Dogra, Sudip; Sen, Subhadeep; Langal, Kamalendu (International Journal of Computer Sciences and Engineering, 2025)
The world is changing day by day. We are moving from analog to digital system in almost every field. If we say for example, our old Television system has now been replaced by digital Television system. Even our cellular phones are becoming smarter. To make our home smarter and digital there are several projects going on. In this work we have designed & developed a prototype for home automation where one can control, monitor and remotely access their home appliances. In this project we have replaced our old switches used in switch board by digital keys. One can control their home appliances even they are not present in their home by their mobile phone and can also get the status of the appliances and power, through their mobile phone. This system will not only give the control of their home appliances, it will also make home smarter digital system and help peoples to keep away from electric shock.